Agreement and Reliability of Lateral Patellar Tilt and Displacement following Total Knee Arthroplasty with Patellar Resurfacing - Kleimeyer, John P.; McQuillan, Thomas J.; Arsoy, Diren; Aggarwal, Vinay K.; Amanatullah, Derek F. (The Journal of Knee Surgery, 2019)
Patellar position and alignment may be measured on routine axial radiographs by various techniques; however, the agreement and reliability of such measurements with a resurfaced patella remain unknown. This study evaluated the range and reliability of lateral patellar tilt and lateral patellar displacement following total knee arthroplasty (TKA) with a resurfaced patella among three observers on 45° Merchant view in 139 TKAs. Intraclass correlation coefficient (ICCs) were used to evaluate intraobserver agreement (IOA) and inter-rater reliability (IRR). IRR was high between each of the observers for lateral patellar tilt (ICC = 0.8) and lateral patellar displacement (ICC = 0.87). IOA was also high upon repeat measurement for the same observer for lateral patellar tilt (ICC ≥ 0.90) and lateral patellar displacement (ICC ≥ 0.86). Therefore, lateral patellar tilt and lateral patellar displacement are reproducible measurements of patellar position on a Merchant axial radiograph following a well-functioning TKA with a resurfaced patella.
Keywords: total knee arthroplasty; patellar resurfacing; patellar tilt; patellar displacement